Does cruciate retention primary total knee arthroplasty affect proprioception, strength and clinical outcome? - Vandekerckhove, Pieter-Jan T. K.; Parys, Roel; Tampere, Thomas; Linden, Patrick; Van den Daelen, Luc; Verdonk, Peter C. (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2015)
Purpose It remains unclear what the contribution of the PCL is in total knee arthroplasty (TKA). The goal of this study was to investigate the influence of the PCL in TKA in relationship to clinical outcome, strength and proprioception. Methods Two arthroplasty designs were compared: a posterior cruciate-substituting (PS) and a posterior cruciate-retaining (CR) TKA. A retrospective analysis was performed of 27 CR and 18 PS implants with a minimum of 1 year in vivo. Both groups were compared in terms of clinical outcome (range of motion, visual analogue scale for pain, Hospital for Special Surgery Knee Scoring system, Lysholm score and Knee Injury and Osteoarthritis Outcome Score), strength (Biodex System 3 Dynamometer ® ) and proprioception (balance and postural control using the Balance Master system ® ). Each design was also compared to the non-operated contralateral side in terms of strength and proprioception. Results There were no significant differences between both designs in terms of clinical outcome and strength. In terms of proprioception, only the rhythmic weight test at slow and moderate speed shifting from left to right was significant in favour of the CR design. None of the unilateral stance tests showed any significant difference between both designs. There was no difference in terms of strength and proprioception between the operated side and the non-operated side. Conclusion Retaining the PCL in TKA does not result in an improved performance in terms of clinical outcome and proprioception and does not show any difference in muscle strength. Level of evidence III.